The Evolution of Guardianship in the Religious Culture: From Terminology to Children's Welfare - Aulia, Hilyati; Hapsin, Abu; Junaidi, Akhmad Arif; Himawanti, Izza; Novita Fauziah (Mimbar Agama Budaya, 2025)
This article investigates the evolution of guardianship in Islamic discourse, focusing on the tension between its traditional rigidity and emerging flexibility. Conventional interpretations, often shaped by patriarchal readings of Quranic texts, have historically assigned guardianship exclusively to men. However, contemporary legal and contextual approaches increasingly recognize women’s eligibility as guardians. Using a qualitative method based on a systematic literature review, this study examines primary Quranic sources alongside family law reforms in selected Muslim-majority countries. The findings reveal a paradigmatic shift from male-centered authority to a child-centered model that prioritizes the best interests of the child. The article also clarifies the conceptual distinction between guardianship pertaining to legal and financial responsibilities- and custody, which addresses emotional and physical support. This shift reflects broader movements to ward egalitarian interpretations and universal child welfare principles within the religious culture frameworks.